1990
DOI: 10.1079/bjn19900074
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonyl-CoA mutase (EC5.4.99.2) and methionine synthetase (EC2.1.1.13) in the tissues of cobalt–vitamin B12deficient sheep

Abstract: The changes in the activities of the two vitamin B,,-dependent enzymes methylmalonyl-CoA mutase (EC 5.4.99.2) and methionine synthetase (5-methyltetrahydrofolat~homocysteine methyltransferase, EC 2.1.1.13) are described in two groups of sheep maintained for 20 weeks on either a cobalt-deficient or a Co-sufficient whole-barley diet. At the end of that period, the plasma concentrations of vitamin B,, were depressed and those of methylmalonic acid were raised in the Co-deficient group. During the course of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
3
36
0
Order By: Relevance
“…Significantly, virtually all of the enzyme in brain was holoenzyme. In other tissues this fraction ranged from 0.3 to 0.6 which is consistent with previous observations in rodents and sheep [5,6,51]. Because The cloning and characterization of murine MCM was undertaken to develop the mouse as a model for molecular genetic investigations of the role that MCM plays in homoeostasis and disease.…”
Section: Holoenzymesupporting
confidence: 70%
See 1 more Smart Citation
“…Significantly, virtually all of the enzyme in brain was holoenzyme. In other tissues this fraction ranged from 0.3 to 0.6 which is consistent with previous observations in rodents and sheep [5,6,51]. Because The cloning and characterization of murine MCM was undertaken to develop the mouse as a model for molecular genetic investigations of the role that MCM plays in homoeostasis and disease.…”
Section: Holoenzymesupporting
confidence: 70%
“…Variability in the level of MCM enzyme activity has been described previously. In sheep and rats, the highest levels of MCM activity were reported in the kidney and liver followed by brain, intestinal mucosa and skeletal muscle [4][5][6]51]. Our [21,26], and that overexpression of MCM in fibroblasts and hepatoma cells does not increase propionate flux above normal [33].…”
Section: Holoenzymementioning
confidence: 96%
“…Moreover, cyanocobalamin, by acting as an enzymatic co-factor to methylmalonyl-CoA mutase enzyme, can also contribute to reduced circulating NEFA (Kennedy et al, 1990). The cyanocobalamin is a vitamin B involved in the synthesis of methionine, a donator of methyl for choline and carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Methylmalonyl-CoA mutase, a mitochondrial enzyme, involved in the conversion of propionate to succinyl-CoA, is an important vitamin B12-dependent gluconeogenic substrate (Kennedy et al, 1990). An inadequate supply of vitamin B12, especially in the early lactation, could possibly lead to decreased function of methylmalonyl-CoA mutase, and hinder energy production from propionate, thus leading to enhanced ketogenesis in the animal.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B 12 acts as a co-factor for methylmalonyl-CoA mutase and methionine synthase which are important for gluconeogenesis and methionine synthesis. It has been reported that low level of dietary Co can lead to vitamin B 12 defi ciencies clinically manifested as anaemia, inappetence and poor production and biochemically characterized by decrease in the plasma concentration of vitamin B 12 , elevations in the plasma concentrations of methylmalonic acid (MMA) and methionine in ruminants (Kennedy et al, 1990). Copper (Cu) is required for the activity of enzymes associated with iron (Fe) metabolism, normal red blood cell formation and wool pigmentation.…”
Section: Introductionmentioning
confidence: 99%